A Study of awareness, attitude and practice of pharmacovigilance among health care professionals in a tertiary care teaching hospital in Bareilly, India - Singh, Krishna; Sayedda, Kauser; Bhardwaj, Richa; Yadav, Neha; Ahmed, Quazi Shahir (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Awareness towards Pharmacovigilance among health professionals in any hospital is an important part of health care system. So, the present study was conducted to know the extent of awareness of Pharmacovigilance among health care professionals. Methods: A cross-sectional questionnaire based study about knowledge, attitude and practices towards adverse drugs reaction (ADRs) and Pharmacovigilance was carried out at Shri Ram Murti Smarak Institue of Medical Sciences, Bareilly (U.P). 153 questionnaires were distributed among the Post graduate students, faculties, interns, nurses and pharmacists. 2-3 days time was given to fill the questionnaire. Results: Out of 153 questionnaires distributed, 99 filled forms were turned up for evaluation. Hence, response rate was 64.70%. 73.33% PGs, 100% faculty members, 53.33% interns, 36% nurses and 18.75% pharmacists were aware of adverse drugs reactions (ADRs) and Pharmacovigilance. Regarding reporting of ADRs, 86.66% PGs, 91.66% faculties, 73.33% interns, 88% nurses and 81.25% pharmacists were agreed to report ADR as it is mandatory and related to increased patients’ safety. Regarding discouraging factors for practice of reporting ADRs, 20% PGs, 16.66% faculties, 80% interns, 40% nurses and 68.75% pharmacists found ADR forms difficult to be filled. According to 66% faculties, 80% PGs, 66.66% interns managing patients are more important than reporting ADRs while 93.75% nurses and 76% pharmacists did not know how to report and where to report. Conclusions: The results of our study indicate that the acceptable number of health-care professionals had a good knowledge and attitude towards pharmacovigilance. There was a huge gap between the ADR experienced, and ADR reported by the health-care professionals. So, there is need of conductance of CMEs, workshops and seminars related to pharmacovigilance for all heaith care professionals especially nurses and pharmacists so, that whole community can be benefitted.